2015
DOI: 10.1017/s095439451500006x
|View full text |Cite
|
Sign up to set email alerts
|

Country ideology and the California Vowel Shift

Abstract: Addressing the dearth of variation research in nonurban, noncoastal regions of California, this study examines the extent to which speakers in Redding, an inland community just north of the Central Valley, participate in the California Vowel Shift (CVS). We acoustically analyze the fronting of the back vowels boot and boat, the raising of ban and backing of bat, and the merger of bot and bought, in sociolinguistic interviews with 30 white lifelong residents. Results reveal a change in apparent time for all ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 42 publications
(60 reference statements)
1
54
1
Order By: Relevance
“…These findings demonstrate that, with respect to a linguistic sense of place, spaces can acquire linguistic meaning at numerous scale levels, with speakers' neighborhood-based, city-based, and region-based identities often interacting with one another (see e.g., Becker 2009). Podesva et al (2015) found that Redding-area speakers' orientation to "town" vs.…”
Section: Enregistermentmentioning
confidence: 99%
“…These findings demonstrate that, with respect to a linguistic sense of place, spaces can acquire linguistic meaning at numerous scale levels, with speakers' neighborhood-based, city-based, and region-based identities often interacting with one another (see e.g., Becker 2009). Podesva et al (2015) found that Redding-area speakers' orientation to "town" vs.…”
Section: Enregistermentmentioning
confidence: 99%
“…Campbell‐Kibler ; Podesva et al. ) has shown that hearers perceive meanings as a function of their perceptions of the context of utterance. This work is extremely promising, but in its early stages.…”
Section: Fields Of Evidence For Social Meaningmentioning
confidence: 99%
“…in press); the parallel fronting of /ow/ after coronals ( Toe ) and non‐coronals ( Boat ) and of /uw/ after coronals ( Too ) and non‐coronals ( Boot ) (Eckert ; Podesva et al. ).…”
Section: Fields Of Evidence For Social Meaningmentioning
confidence: 99%
“…But recent work has also found the feature in speakers from less‐urban, inland communities in California as well, though to a lesser degree than on the coasts (Podesva et al. in press). Thus, while the change appears to have originated in urban, coastal communities of California, its wide reach makes the feature associable with the state as a whole.…”
Section: Introductionmentioning
confidence: 96%